Immunological detection of serum antibodies in pediatric medical workers exposed to varying levels of SARS-CoV-2. Issue 1 (January 2021) - Tu, Danna; Shu, Junhua; Wu, Xiaoli; Li, Heng; Xia, Zhi; Zhang, Yanfang; Fang, Yaohui; Shen, Shu; Guan, Wuxiang; Wang, Hualin; Huang, Zhaoxuan; Wang, Guirong; et al.
Highlights: Pediatric healthcare workers are at risk for SARS-CoV-2 transmission from children and aerosols increase SARS-CoV-2 infection rate. ELISA and dual-target fluorescence accurately detect SARS-CoV-2 antibodies indicated that antibody detection should be considered as an auxiliary diagnosis of COVID-19. Antibody positive subjects tested negative for SARS-CoV-2 neutralizing antibodies and SARS-CoV-2 antibodies diminish to near undetectable levels within two months.